Optimizing the Interventional Cardiology Facility: Services Integration in Routine Workflow - Gortzis, L.; Kalogeropoulos, A.; Alexopoulos, D.; Nikiforidis, G. (Methods of Information in Medicine, 2007)
Objectives: Integration of administrative and clinical data, imaging, and expert services, although challenging, is a key requirement in contemporary interventional cardiology facilities (ICF). We propose a workflow-oriented hybrid system to support the ICF and investigate its feasibility and effectiveness in a referral medical center.Methods: We have developed a Java-powered hybrid system (NetCARDIO), able to support over web synchronous and asynchronous data management, realtime multimedia data telemonitoring and continuous telementoring. Data regarding procedural rates, treatment planning and radiation exposure were collected over a two-year period of routine NetCARDIO implementation (July 2002 to June 2004) and compared with data from an immediately preceding period of equal duration (January 2000 to December 2001).Results: During the NetCARDIO period, 163 ±11 coronary procedures per month were performed vs. 77 ±15 during the control period (p <0.001). Percutaneous coronary intervention was delivered ‘ad hoc’ in 88% of eligible patients vs. 45% (p <0.001). Mean fluoroscopy time per coronary lesion treated decreased from 594 ± 82sto 540 ±94s (p < 0.001). Annual radiation exposure of expert interventionistswas decreased by 22%. Electronic storage significantly reduced archiving costs.Conclusions: Real-time multimodal services sharing combined with powerful database capabilities is feasible through a web-based structure, significantly enhancing performance and cost-effectiveness of ICF. Further research is needed to promote integration of additional data sources and services.
Keywords: Medical services integration; medical informatics; Java; JMF; radiation exposure; interventional cardiology; heath services research; cost analysis; collaborative services; medical education; hybrid systems